Integrated proteomic and metabolomic analysis elucidates the effects and mechanisms of Qiziyusi decoction on IVF outcomes in advanced maternal age infertility - Jin, Qingmei; Zhao, Jianyun; Ma, Yingjie; Zhang, Yi; Yan, Menghan; Song, Jingyan; Cao, Xianling; Sun, Zhengao (Frontiers in Endocrinology, 2025)
BackgroundAdvanced maternal age (AMA) is associated with increased infertility and poor outcomes of in vitro fertilization (IVF), with limited effective treatments available. The traditional Chinese medicine (TCM) formula Qiziyusi decoction (QZYSD) is promising for addressing infertility in older women; however, its effects and mechanisms on IVF outcomes remain poorly understood. This study integrated a prospective cohort study, proteomics, and metabolomics to elucidate the effects and mechanisms by which QZYSD improves IVF outcomes in AMA infertility.MethodsThis prospective cohort study included 87 patients with tubal factor infertility who underwent IVF at the Reproductive and Genetic Center of Shandong University of TCM from April 2019 to October 2020, and stratified according to maternal age into the AMA (≥ 35 and ≤ 41), AMA-QZYSD (≥ 35 and ≤ 41), and young maternal age (YMA; ≥ 21 and ≤ 27) groups. The three groups of patients underwent controlled ovarian hyperstimulation using a short luteal phase protocol. In the AMA-QZYSD group, patients started oral administration of QZYSD from the day of pituitary downregulation until the day of oocyte retrieval, and follicular fluid (FF) was collected from all groups. The effects of QZYSD on improving IVF outcomes in AMA infertility were evaluated primarily by assessing cumulative clinical pregnancy (CCP) and miscarriage (CCM) rates, with secondary endpoints including the duration and dosage of gonadotropin (Gn) use, serum levels of follicle stimulating hormone (FSH), luteinizing Hormone (LH) and estrogen (E2) after pituitary downregulation, serum levels of E2 and progesterone (P) on the day of human chorionic gonadotropin (hCG) administration, endometrial thickness (EMt), number of oocytes retrieved, fertilization and cleavage rates, number of high-quality embryos on day 3, and embryo freezing status. Differential metabolites and proteins in FF were detected using ultra-performance liquid chromatography-tandem mass spectrometry and label-free quantitative proteomics. Correlation analysis was conducted to identify metabolites and proteins with significant correlations, and potential pathways were enriched and constructed using the common pathway analysis function in MetaboAnalyst (version 5.0). Finally, a “core target protein-metabolite-signaling pathway” network diagram was constructed using Cytoscape to further elucidate the mechanisms by which QZYSD improves IVF outcomes in patients with AMA infertility.ResultsThe study included 87 patients in the AMA-QZYSD experimental (n = 28), AMA control (n = 28), and YMA (n = 31) groups. The baseline demographic and clinical characteristics, such as maternal and paternal age, antral follicle count, basal serum levels of FSH, and E2 levels, were comparable across the groups. Regarding the primary endpoint, there was a trend toward a higher CCP rate in the AMA-QZYSD group compared to the AMA group. However, this difference was statistically non-significant (53.57% vs. 39.29%, P = 0.28), while the CCP rate in the AMA group was significantly lower than in the YMA group (P < 0.05). The CCM rates indicated non-significant differences among the three groups (P > 0.05). For the secondary endpoint, serum levels of E2 on the day of HCG (2391.57 ± 985.09 versus 1833.39 ± 763.49, P = 0.04), the number of retrieved oocytes (9.18 ± 3.90 versus 7.07 ± 2.92, P = 0.04) and high-quality embryos on day 3 (1.86 ± 1.58 versus 1.04 ± 1.20, P = 0.05) were slightly higher in the AMA-QZYSD group compared to the AMA control group, but both were lower than the YMA group (P < 0.05). There were non-significant differences between the AMA-QZYSD and AMA groups regarding Gn usage days, Gn dosage, serum levels of FSH, LH and E2 after pituitary downregulation, serum levels of P on the day of hCG administration, EMt, IVF 2PN fertilizations, and embryo freezing status (P > 0.05). A total of 35 differentially abundant metabolites were identified through metabolomics, and 492 differential proteins were detected using proteomics. The integrated metabolomics and proteomics results suggested that QZYSD may improve IVF outcomes in AMA infertility primarily by regulating the expression of component C8 alpha chain (C8A), carboxypeptidase B2 (CPB2), serum paraoxonase/arylesterase 1 (PON1), immunoglobulin heavy variable 3-9 (IGHV3-9) and pantetheinase (VNN1), as well as influencing the protein digestion and absorption and pantothenate and coenzyme A biosynthesis pathways.ConclusionQZYSD in IVF for women with AMA infertility is promising for improving clinical pregnancy rates and overall IVF outcomes, potentially through its effect on the FF microenvironment. However, further research is needed to conduct larger randomized controlled double-blind clinical trials and experimental studies to elucidate the efficacy and mechanisms of QZYSD on IVF success in this population.